Molecular Dynamics Studies: The Interaction Of Erythromycin A With A Single Base Substitution Of 50s Ribosomal Subunit - Mohamad Zobir, Siti Zuraidah (2012)
The objective of the study is to find how the interactions erythromycin A (ERYA), a 14-membered ring macrolide, with a single base substitution from adenine to guanine on the large ribosomal subunit at 2041. This single base substitution has been reported of to be one of the resistance modes in the binding of macrolides. Molecular dynamics (MD) simulation is a great tool that was used in this study to explain at the molecular level why resistance happens when a single base substitution takes place at 2041, one of the residues in PTe.